Successful treatment with transjugular intrahepatic portosystemic shunt (TIPS) of recurrent massive rectal bleeding due to portal hypertension: Case report - Yakup YEŞİLKAYA and Barbaros ÇİL and Bora PEYNİRCİOĞLU and; s Şimşek (Turkish Journal of Gastroenterology, 2019)
-